ON THE QUESTION OF THE METHODS OF TEACHING THE RUSSIAN LANGUAGE TO A BILINGUAL AUDIENCE (Web of Teachers: Inderscience Research, 2024)
This article discusses the development of methods for teaching the Russian language, taking into account the specifics of a bilingual audience. The emphasis is on the fact that when developing methods for teaching the Russian language, it is necessary to clearly understand not only the educational problem and the purpose of study, but also the specifics of the bilingual audience.